Analysis of Numeracy Literacy for each Student's Learning Style through Differentiated Learning assisted by ORIENT based on Thinglink - Munahefi, Detalia Noriza; Maharani, Sintya; Khoirunnisa’, Danika Dian; Azzahra, Nailin Nafiah; Maulana, Mirza; Budianto, Angela Vivian (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
Numeracy literacy is an ability that junior high school students must have. The facts show that junior high school students' numeracy literacy is still low because learning activities are not supported by learning media that can optimize the performance of students with various learning styles. The research aims to analyze the numeracy literacy of each student's learning style through differentiation learning assisted by thinglink-based geometry in learning style (ORIENT) media. The research method is a combination of sequential explanatory which begins with quantitative data analysis followed by qualitative data. The population is class VIII students at State JHS 22 Semarang. Samples were taken using the cluster random sampling technique. The results of the mean difference test with the Wilcoxon test show a significance value of 0.000 < 0.05 so there is an increase in students' numeracy literacy with ORIENT-assisted differentiation learning. The N-gain result of 0.4031 shows that there is an increase in numeracy literacy in the medium category. Students with an auditory learning style have difficulty analyzing information. Students with a visual learning style have difficulty using mathematical skills in making decisions. Students with a kinesthetic learning style have difficulty using numbers or mathematical symbols. Literasi numerasi merupakan kemampuan yang harus dimiliki oleh siswa sekolah menengah pertama. Fakta menunjukkan bahwa literasi numerasi siswa SMP masih rendah dikarenakan kegiatan pembelajaran yang tidak didukung dengan media pembelajaran yang mampu mengoptimalkan kinerja siswa dengan berbagai gaya belajar. Penelitian bertujuan menganalisis literasi numerasi tiap gaya belajar siswa melalui pembelajaran diferensiasi berbantuan media geometry in learning style (ORIENT) berbasis thinglink. Metode penelitian yakni kombinasi sequential explanatory yang diawali dengan analisis data kuantitatif dilanjutkan data kualitatif. Populasi yakni peserta didik kelas VIII SMP Negeri 22 Semarang. Sampel diambil dengan teknik cluster random sampling. Hasil uji beda rataan dengan uji Wilcoxon menunjukkan nilai signifikansi 0,000 < 0,05 sehingga terdapat peningkatan literasi numerasi siswa dengan pembelajaran diferensiasi berbantuan ORIENT. Hasil N-gain 0,4031 menunjukkan terdapat peningkatan literasi numerasi dalam kategori sedang. Siswa dengan gaya belajar auditori mengalami kesulitan dalam menganalisa informasi. Siswa dengan gaya belajar visual mengalami kesulitan menggunakan kemampuan matematika dalam mengambil keputusan. Siswa dengan gaya belajar kinestetik mengalami kesulitan dalam penggunaan angka atau simbol-simbol matematika.